(untitled) (International Journal of Engineering and Computer Science, 2016)
Identification of the plant diseases is the key to preventing the losses in the yield and quantity of the agricultural product. The studies of the pomegranate plant diseases mean the studies of visually observable patterns seen on the plant. It is very difficult to monitor the pomegranate plant diseases manually. Hence, image processing is used for the detection of pomegranate plant diseases. Disease detection involves the steps like image acquisition, image pre-processing, image segmentation, statistical feature extraction and classification. K-means clustering algorithm is used for segmentation and support vector machine is used for classification of disease.